Optimizing the Role of Family as Main Support for Elderly Through Social Counseling - Rizqi Alamsyah; Muhamad Khasbi Hanif; Habieb Abdillah Ali Affaf; Ulin Nihayah (Istisyarah: Jurnal Bimbingan Konseling Islam, 2025)
Indonesia is undergoing a rapid demographic transition toward an aged society, shifting the long-term caregiving burden heavily onto the informal family structure. Within the local sociocultural context of filial piety, the family is the primary pillar of eldercare. However, modern socioeconomic pressures have eroded domestic capacities, trapping productive-age individuals within a highly stressful dual-obligation matrix known as the "Sandwich Generation." This study aims to evaluate the multidimensional caregiver burden experienced by the Indonesian sandwich generation and explore the effectiveness of transforming the Bina Keluarga Lansia (BKL) [Family Development for the Elderly] program through digitalized, contextual social counseling interventions. Operating as a systematic literature review and qualitative metasynthesis, this study comprehensively analyzed empirical, peer-reviewed literature (n = 25) published between 2015 and 2025. Data selection strictly followed the PRISMA protocol, extracting variables linked to family support, caregiver burden (via the Zarit Burden Interview framework), and social work counseling models. The synthesis demonstrates a critical geriatric competence gap within households. Traditional top-down medical interventions routinely fail because they ignore the caregiver's psychosocial ecosystem. Applying the Elaboration Likelihood Model (ELM), this study reveals that digitalizing social counseling (e.g., via asynchronous psychoeducational platforms and interactive peer support groups) effectively bypasses caregiver time poverty, reduces social isolation, and significantly lowers perceived caregiver burden scores. Social counseling acts as a transformative mechanism that shifts the family’s role from a passive, overwhelmed shelter into a highly competent, resilient support system. To sustain this framework, macro-level policy adjustments are urgently required, including the institutionalization of community-based respite care, targeted fiscal incentives for low-income caregiving households, and the structural revitalization of the BKL curriculum to incorporate stress management and digital health literacy.